2010
DOI: 10.1177/1744987109357816
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial of clinical supervision: selected findings from a novel Australian attempt to establish the evidence base for causal relationships with quality of care and patient outcomes, as an informed contribution to mental health nursing practice development

Abstract: This paper reports on selected findings from a novel randomised controlled trial (RCT) conducted in mental health settings in Queensland, Australia. Several national and state reports recently revealed the sub-optimal state of Australian mental health service provision which have direct implications for mental health nursing, including the privately experienced cost of working and coping in these settings. Clinical supervision (CS), a structured staff support arrangement, has shown promise as a positive contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
136
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 33 publications
3
136
0
3
Order By: Relevance
“…In addition, this study reveals that CS definitely influences the development of skills important for patient safety care (see Table 2). The links between CS and patient safety are discussed in the literature [38,44,45] and Dawson [38] suggested that the former has some positive impact on the latter. Sullivan et al [29] highlighted that nurses need to be prepared for their future professional practice with tools in the form of knowledge, skills and attitudes, enabling them to continuously improve the quality and safety of care.…”
Section: The Relationship Between Cs and Patient Safetymentioning
confidence: 99%
“…In addition, this study reveals that CS definitely influences the development of skills important for patient safety care (see Table 2). The links between CS and patient safety are discussed in the literature [38,44,45] and Dawson [38] suggested that the former has some positive impact on the latter. Sullivan et al [29] highlighted that nurses need to be prepared for their future professional practice with tools in the form of knowledge, skills and attitudes, enabling them to continuously improve the quality and safety of care.…”
Section: The Relationship Between Cs and Patient Safetymentioning
confidence: 99%
“…It has been suggested that clinical supervision practice, in its present variable form, may not represent good value or good practice when it is applied across-the-board within health services (White & Winstanley, 2010). Consistent with all health service practice, clinical supervision implementation needs to be based on sound evidence.…”
Section: Resultsmentioning
confidence: 99%
“…It may be that findings of supervision ineffectiveness derive from studies where supervisors lacked the expertise to fulfill the educational function, resulting in the delivery of sub-standard supervision. Some researchers have suggested that ineffective supervision may be harmful for supervisees and service recipients (Ellis, 2010;Gaitskell & Morley, 2008;White & Winstanley, 2010), highlighting this potential risk and the need to establish the antecedents of effective supervision (Watkins & Milne, 2014).…”
Section: Effectiveness Of Clinical Supervisionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within such research, results are often mixed. While some studies indicate that supervision can have a positive impact on patient outcomes (Bambling, King, Raue, Schweitzer, & Lambert, 2006;Ost, Karlstedt, & Widen, 2012), other research finds no impact (White & Winstanley, 2010). …”
Section: An Experimental Study Of the Role Of Therapist Gender And Anmentioning
confidence: 99%